Disponibilidade hídrica na germinação de sementes e no crescimento de plântulas da leguminosa forrageira Macrotyloma axillare (E. Mey) Verdc. cv. Java - Paiva, Auricleia Sarmento de [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
The objective of this research was to evaluate physiological characteres of the tropical forage legume, Macrotyloma axillare cv. Java (perennial horse gram) submitted to different water potentials and to determine the physiological quality of three seed lots of this cultivar. The physical purity, 1000 seeds weight, standard germination test (SGT) and speed of germination index (SGI) were evaluated. The following vigour tests were performed: first count of SGT; electrical conductivity and accelerated aging. The effect of substratum water availability was studied using polyethylene glicol solutions (PEG 6000) on seed germination and soil with three levels of water contents (60, 45 and 35% of field capacity) on germination and early growth of seedlings. Differences on initial physiological potential of scarified seeds could be observed by the germination test. First count of germination and SGI were not sensible to detect differences in seed physiological potential of these three lots. The accelerated aging of scarified seeds can be performed at 41ºC during at least 72 hours or at 45ºC for 48 hours. The electrical conductivity test was adequate to differentiate lots of scarified seeds after 48 hours of imbibition. The seed lot number three was classified as the lowest vigour lot of perennial horse gram seeds. There was progressive and significant decrease of germination percentage and of SGI when the substratum water potential decreased from zero to -0,6 MPa and reduction of germination percentage and SGI when the soil water availability decreased from 60% to 45 and 35% of field capacity. All seedlings shoot characters were hastened by the decrease of soil water availability, mainly the parameters: seedling height, fresh mass and area of leaves... (Complete abstract, click electronic access below)

Objetivou-se avaliar características fisiológicas da leguminosa forrageira tropical, Macrotyloma axillare cv. Java (macrotiloma) submetida a diferentes potenciais hídricos e determinar a qualidade fisiológica de três lotes de sementes dessa cultivar. Determinou-se a pureza física dos lotes, o peso de mil sementes, o teste padrão de germinação (TPG) e o índice de velocidade de germinação (IVG). Os seguintes testes de vigor foram realizados: primeira contagem do TPG, condutividade elétrica e envelhecimento acelerado. Avaliou-se o efeito da disponibilidade hídrica do substrato sobre a germinação de sementes com o uso de soluções de Polietileno Glicol (PEG 6000) e a germinação e o crescimento inicial das plântulas sob diferentes disponibilidades hídricas no solo (60, 45 e 35% da capacidade de campo). Diferenças no potencial fisiológico inicial de sementes escarificadas puderam ser observadas pelo teste de germinação. Os testes de primeira contagem e IVG não foram sensíveis para detectar diferenças no potencial fisiológico das sementes dos três lotes estudados. O envelhecimento acelerado das sementes escarificadas pode ser realizado a 41º C por um período mínimo de 72 horas ou a 45º C durante 48 horas. O teste de condutividade elétrica mostrou-se adequado para diferenciar os lotes de sementes escarificadas, a partir de 48 horas de embebição. O lote 3 foi classificado como o lote de menor vigor. Houve redução progressiva e significativa da porcentagem de germinação e do IVG quando o potencial hídrico do substrato decresceu de 0,0 até -0,6 MPa e decréscimo na germinação e no IVG quando a disponibilidade hídrica no solo decresceu de 60% para 45 e 35% da capacidade de campo. Todas as características da parte aérea das plântulas foram prejudicadas pela redução da disponibilidade hídrica do solo, notadamente, os parâmetros altura de plântula,...
Keywords: Sementes - Qualidade; Germinação; Potencial hídrico; Macrotiloma; Altura de plântula; Água no solo; Water potential; Physiological quality; Seedling height; soil water; Perennial horse gram